A housing delivery scheme through the cooperative approach - Nzeamalu, Innocent Chizoba (1988)
The housing need particularly that of the working masses continues to be a major problem facing the government of the Philippines today. The government has continued the development of housing delivery through its own agencies and through the encouragement of the private sector leaving the cooperative approach unattended to. Specifically, this study attempted to: 1) asses the status of housing cooperatives in the Philippines; 2) find out why housing cooperative system has not fully been explored in the housing delivery; 3) propose a cooperative housing delivery sytem; 4) identify conditions for a successful housing cooperative; 5) identify the role of the government in the growth of housing cooperatives; and 6) assess the prospects of the cooperative housing system in the Philippines. The content analysis research method is used in this study to elicit insights on the development of the cooperative system in general in the Philippines while the case study method was used mainly to assess the degree of success and problems of some of the existing housing cooperatives which helped the researched in coming up with a definite scheme for the effective exploration of the coopeartive system for the delivery of housing to the intended group. The findings of this study showed; 1) while the number of housing cooperatives officially registered with the Bureau of Cooperatives Development decreased from 10 in June 1972 to only 6 as of March 31, 1988, there is a part of the country due to the interests showed by the non-governmental organizations in the housing cooperative development; 2) the housing cooperative system in the Philippines has not been fully explored because the national housing policy and the national financing system have no law within it that provided for the special features of the housing cooperative system; 3) there are government housing and financing agencies that are well suited for the establishment of housing cooperative system; 4) government must always play a role in the policy formulation and legislation, regulation and other measures in housing cooperative to enable it to grow; and, 5) the condition for a successful cooperative education and training, good management, a coordinating body, a strong moral and financial backing, land affordability and homogeneity of members. The conclusions to be derived from this study is that the development of cooperatives in the Philippines have been mainly designed for the agricultural sector and this made it difficult for the housing cooperative system to contribute its share to the solution of the housing problem. The development of the housing cooperatives has been haphazard, to say the least, and to properly harness the potentials of the cooperative principles in housing, a special legislation which recognizes the distinct features of this type of organization is vital in protecting the housing cooperative structure and providing technical and financial support
Vita.
Thesis (Master of Architecture)--University of the Philippines, Diliman
Keywords: Housing, Cooperative -- Philippines